2023
DOI: 10.1002/cmdc.202300035
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Polymers Functionalized with Histidine and Carcinine as Chelating Therapeutics for Copper Dyshomeostasis

Abstract: In recent years, cyclodextrin polymeric nanoparticles have been designed to introduce new properties and extend their medical applications. Based on the features of cyclodextrins, we derivatized cross‐linked cyclodextrin polymers with histidine or carcinine moieties. We found that amylases do not hydrolyze cyclodextrin polymers. The new polymers can form copper(II) complexes and may act as nanochelators to counteract copper(II) dyshomeostasis‐related diseases. Furthermore, the copper(II) complexes show superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Consequently, some of the strategies currently being pursued to address the emergence of PD rely on the development of antioxidant systems able to prevent the accumulation of ROS or to inhibit the formation of α-synuclein aggregates. [14] Considering the major role of superoxide radicals in ROS generation, [17] research on antioxidant systems has centered on the development of small ionophores whose Cu II , [18][19][20][21][22][23][24][25] Fe II , [18] Mn II , [18,26,27] and Zn II [28] complexes present superoxide dismutase (SOD) activity. Although very few such systems have yet displayed satisfactory clinical results, [29,30] the use of tetraazamacrocycles and nanotechnology are two of the emerging promising approaches to tackle neurodegenerative diseases involving oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, some of the strategies currently being pursued to address the emergence of PD rely on the development of antioxidant systems able to prevent the accumulation of ROS or to inhibit the formation of α-synuclein aggregates. [14] Considering the major role of superoxide radicals in ROS generation, [17] research on antioxidant systems has centered on the development of small ionophores whose Cu II , [18][19][20][21][22][23][24][25] Fe II , [18] Mn II , [18,26,27] and Zn II [28] complexes present superoxide dismutase (SOD) activity. Although very few such systems have yet displayed satisfactory clinical results, [29,30] the use of tetraazamacrocycles and nanotechnology are two of the emerging promising approaches to tackle neurodegenerative diseases involving oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Although very few such systems have yet displayed satisfactory clinical results, [29,30] the use of tetraazamacrocycles and nanotechnology are two of the emerging promising approaches to tackle neurodegenerative diseases involving oxidative stress. [20][21][22][23][24][31][32][33][34] In this context, we have recently observed that the modification of non-toxic boehmite nanoparticles (BNPs) with binuclear Cu II azamacrocycles can significantly enhance the SOD activity of such complexes. [25,31,33,35] But there is little point in eliminating ROS without disrupting the source that generates them, which are the α-synuclein peptide aggregates in the case of PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation